The Role of Internet Community in Political Elite's Sociopolitical Discourse - Akopov, Grigory Leonidovich; Akopova, Anna Leonidovna; Pankova, Galina Konstantinovna; Puiy, Anatoli Stepanovich; Redkina, Tamara Yurevna (International Review of Management and Marketing, 2015)
The intensive development of information and communication technologies has caused various transformations in the sociopolitical discourse. The Internet community has adopted a new role – that of an interactive platform which enables real-time communication for representatives of the government, political elites and electorate. Members of Internet communities can exchange all types of information. So, the possibility of network interaction made possible public participation in the sociopolitical process. Thence, the Internet community may be capable of influencing political elites and representatives of governmental structures. This mechanism makes it possible to citizens to influence the government. Many politicians have already realized that in the near future, refusing to maintain political dialogue with the Internet community may lead to complete oblivion or even to their demission. Internet activity is gradually becoming one of the criteria of the efficiency of the political activity. The development of the political discourse shows a higher potential of the influence that the Internet community has on the political elites and, thus, on the political processes active in a country and on the democratization of the political power. Political connotations of the Internet community permit the political elites valuate the attitude of the Internet community to main political events and main representatives of the political elites. Keywords: Internet community, blogs, network, information process, network policy, political elite, informational power JEL Classifications: H11; O32; O38; Z13